SURVEY MATHEMATIC ANXIETY BAGI SISWA SEKOLAH DASAR STUDI KOMPARASI : SDIT AL-MUJAHIDIN & MI MIFTAHUDDIN - Diara Rizky Prayitno; Rendy Nugraha Frasandy; Rian Vebrianto (Journal Cerdas Mahasiswa, 2022)
This study aims to map Mathematical Anxiety in elementary school students at SDIT Mujahidin and MI Miftahuddin. There are several studies that have been conducted on this theme but differ in terms of the sample of this study. This research resulted in valuable policy recommendations for educators and government for mapping and how to deal with students' Mathematical Anxiety in order to be ready to face challenges and opportunities in the future. The study used a survey research type with a research sample of 120 students. Respondents in the study consisted of 54 men and 66 women. Furthermore, the instrument used was the Mathematical Anxiety Survey (MAS) which consisted of four constructs with an average Croanbach alpha value with high criteria. The results showed that from the students' perception of Mathematical Anxiety, it could be seen that the Mathematical Anxiety that was owned was quite high from the mathematical anxiety instrument that had been used and tested. From the results of the study, it was found that Mathematical Anxiety on the somatic construct was 62.1%; at the emotional level of 62%; at the cognitive level of 60%; and at the behavioral level that is 58%. Therefore, a solution is needed in dealing with the high level of student anxiety. This research is useful in developing human resources for educators and especially students in dealing with Mathematical Anxiety for students in elementary schools. This study suggests the importance of educators providing solutions to Mathematical Anxiety for students. For this reason, it is necessary for educators who have good enough abilities to help their students in dealing with Mathematical Anxiety